CORRUPTION ERADICATION POLICY IN CHINA DURING XI JINPING ERA - Syam, Firdaus; Fatia, Ummi (Journal of Social Political Sciences, 2022)
The anti-corruption campaign launched by Xi Jinping since the beginning of his tenure as president of China has experienced pros and cons according to some experts in the fields of politics, economics, and law, ranging from a decline in short-term local economic growth, a decline in domestic investment, a camouflage for power struggles, and recovery. public confidence in the Chinese Communist Party. Under Xi Jinping's leadership, the anti-corruption campaign has expanded in scope, from central officials, regional officials, the military, to retirees who previously held certain positions in the Chinese Communist Party. With the descriptive analysis method and elite and power theory, this study focuses on efforts to eradicate corruption in China during the Xi Jinping era, whose implementation is much different from that of previous Chinese leaders.